EQUAL OPPORTUNITY AS THE BASIS FOR SOCIAL-ECONOMIC INTEGRATION OF IMMIGRANTS IN THE EUROPEAN UNION - Cristina, Llano Hermida (Anales Universitatis Apulensis Series Jurisprudentia, 2012)
Equality of opportunities or chances constitutes one of the central notions in the course of approaching the problem of immigration from the perspective of legitimacy. Here, we use the material or substantive concept of equality of opportunities or chances; this is to say that a debate which relies only on the principle of non-discrimination is incomplete. It is indispensible that the immigrant overcomes the original situation of disadvantage; and for this it is indispensible to derive means or measures from the notion of the civil society. Keywords : immigration, equality of opportunities, principle of non-discrimination, civil society, measures.